The effect of restaurant environment on social dining behaviour in fine dining restaurant / Muhammad Shazwan Mohamad Rosli - Mohamad Rosli, Muhammad Shazwan (2021)
Nowadays, the dining environment is very important for restaurants to ensure consumers are comfortable socializing in the dining area they enjoy. It also ensures that the restaurant provides consumers with how long they can relax, socialize and eating. The problems that arise while at the social dining is came through in this study are, the cleanliness of the restaurant in the dining area, the type of food, the quality of service and the environment in restaurant. Social dining behaviour in a dining restaurant is the relationship between the social dining table of the restaurant and the consumer to determine that the table of social dining good in quality of service or feel may be high from warmth and health, the concept of wellbeing. The aim of this study is to see the interior environment aspect which is the circulation between with furniture layout, sound, and material that may effect on behaviours social dining in fine dining restaurant Malaysia that want to cater to their social dining needs. The data was analysed to evaluate and determine level of user satisfaction in social dining at fine dining restaurant and effect of social dining behaviour in design environment in fine dining restaurant. The research shows of the levelling on satisfaction in aspects of interior atmosphere, furniture, and social privacy at the social dining table. The research shows of the levelling on satisfaction in aspects of interior atmosphere, furniture, and social privacy at the social dining table. The results of the research also suggested that it is hope that the research can contribute to the improvement of table-to-table distance, furniture materials, and food table and chair arrangement to improve the level of comfort, mobility, and social in social dining places in order to encourage more people to come and experience the beauty and comfort inside the restaurant feeling happy and satisfied.